The Concentrations of Selected Heavy Metals in the Surface Sediments in Three Locations of Southern Philippines - Gangoso, Sheilane J; Rosario, Romeo M Del; Walag, Angelo Mark P (Asian Journal of Biological and Life Sciences)
Some heavy metals may be nutritionally essential, potentially beneficial, or toxic to life. Yet, frequent exposures to critical metals could also result in severe health and environmental impacts. This study aimed to investigate the coastal sediments of the three locations in the southern Philippines, namely: Oroquieta City, Baliangao, and Alicia, in terms of their concentrations in the following heavy metals: cobalt, chromium, copper, manganese, nickel, cadmium, and lead. The heavy metals in the surface sediment samples from the three locations were analyzed using AAS Perkin Elmer AA200. The results revealed that Oroquieta, Baliangao, and Alicia showed statistically equivalent low concentrations in cobalt, manganese, and lead, which were within the range of 21-29 ppm, 100-129 ppm, and 67-89 ppm, respectively. However, the three locations showed higher and statistically different concentrations of chromium, which was in the range of 672-831 ppm. The three locations also showed statistically different concentrations of copper, manganese, and lead. Of the three locations, nickel was only detected in Oroquieta, with a concentration of nearly 37 ppm. All the heavy metal concentrations, however, did not exceed the safety standards set by government agencies. In addition, there was no cadmium detected from the three locations. Hence, it can be concluded that the three coastal areas are very suitable for marine organisms like seashells and other marine organisms. The human impact has been fairly not alarming in the three sites.
Keywords: Heavy metals; Mindanao coasts; Philippine coasts; Surface sediments; Surface sediments quality